STUDI PEMANFAATAN LIMBAH ABU TERBANG BATUBARA (FLY ASH) DAN KALENG MINUMAN SOFT DRINK SEBAGAI PENGGANTI MATERIAL BAJA RINGAN - Samhuddin, Samhuddin; Sudia, Budiman; Iqwal, La Ode (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The purpose of this research is to know the effect of fly ash addition to the hardness and toughness ofmaterial produced. In this research, it is known that aluminum cans waste as a matrix and ash waste coal flyas reinforcement. The tools and materials used in the research are furnace, ladle, stircoast, blower, sand,pattern, waste cans and coal fly ash waste. This research procedure starts from the process of makingspecimens with alloy (%) aluminum-fly ash. Fariation of aluminum-fly ash alloy is 80%: 20%, 70%: 30%,60%: 40%. In Vickers hardness testing seen at the lowest Al-FA hardness level was on specimens withvariation Al 60%: FA 40% ie 49.78528 kg / mm² and highest Al-FA hardness was in specimens withvariation Al 80%: FA 20 % alloy that is equal to 60,25068 kg / mm². Meanwhile, on the toughness impacttest, the highest impact strength value is in Specimens with Al 60% variation: FA 40% alloy is 0.162 J / mm²and the lowest impact strength is in specimen from 100% Aluminum variation of 0.056J / mm².Keywords: Metal matrix composite, Aluminum, and fly ash